2001
DOI: 10.1103/physrevd.64.083513
|View full text |Cite
|
Sign up to set email alerts
|

Attractors and isocurvature perturbations in quintessence models

Abstract: We investigate the evolution of cosmological perturbations in scenarios with a quintessence scalar field, both analytically and numerically. In the tracking regime for quintessence, we find the long wavelength solutions for the perturbations of the quintessence field. We discuss the possibility of isocurvature modes generated by the quintessence sector and their impact on observations.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 42 publications
2
46
1
Order By: Relevance
“…(9) shows that the growing mode of perturbation during the scaling regime accompanies the adiabatic (δ v ) as well as the isocurvature (S rφ ) modes; this is in contrast with the assumption made in [23], and the result in [31] * . * The work in [31] was made in the zero-shear gauge which fixes the scalar-type shear of the normal hypersurface χ equal to zero [36,40]. δ f in the zero-shear gauge is the same as δ f χ ≡ δ f +3(1+w)Hχ.…”
Section: Perturbed Equationscontrasting
confidence: 46%
See 1 more Smart Citation
“…(9) shows that the growing mode of perturbation during the scaling regime accompanies the adiabatic (δ v ) as well as the isocurvature (S rφ ) modes; this is in contrast with the assumption made in [23], and the result in [31] * . * The work in [31] was made in the zero-shear gauge which fixes the scalar-type shear of the normal hypersurface χ equal to zero [36,40]. δ f in the zero-shear gauge is the same as δ f χ ≡ δ f +3(1+w)Hχ.…”
Section: Perturbed Equationscontrasting
confidence: 46%
“…Although the scaling by itself cannot explain the acceleration in the present epoch, since the scaling works as an attractor we find many implementation of quintessence idea having such an attractor in the early evolution stage. The evolution of perturbation during the scaling regime as well as the following quintessential development has been actively studied in recent literature [3,5,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34].…”
mentioning
confidence: 99%
“…If the field is a tracker, the initial conditions may indeed be irrelevant also for the perturbed field. However, for minimally coupled fields it has been shown that in some instances this is not the case [41,42], while isocurvature perturbations in coupled quintessence remain to be systematically studied.…”
Section: B Perturbation Evolutionmentioning
confidence: 99%
“…This becomes a source of the CMB anisotropy through the Sachs-Wolfe effect. When the slow-roll condition is satisfied for the quintessence,δ Q (k) is approximated as 9) and it changes its behavior at the scale k phys ∼ H 0 or at k phys ∼ Λ 2 /f Q , as a consequence of the scale dependence ofq. Now, we consider the CMB anisotropy in the case with the isocurvature mode.…”
Section: Isocurvature Modementioning
confidence: 99%
“…[6]. #2 Abramo and Finelli [9] studied the isocurvature fluctuations for tracker-type quintessence models without considering the evolution of the tracker field and its fluctuations during inflation.…”
Section: Introductionmentioning
confidence: 99%